Evolutionary history in theological perspective: exploring the scientific story of the cosmos - Russo, Mario Anthony (Lexington Books/Fortress Academic, 2024)
"Evolutionary History in Theological Perspective: Exploring the Scientific Story of the Cosmos argues, with a new theological interpretive lens, that Christian theological interpretations make more compelling sense of evolutionary history than naturalistic or spiritual ones"--